Outcomes of amputation due to long-standing therapy-resistant complex regional pain syndrome type I - Jan H.B. Geertzen; Jelmer Scheper; Ernst Schrier; Pieter U. Dijkstra (Medical Journals Sweden, 2020)
Objective: To assess long-term outcomes of amputation in patients with long-standing therapy-resistant complex regional pain syndrome type I (CRPS-I). Design: Partly cross-sectional, partly longitudinal study. Subjects: Patients who had amputation of a limb due to long-standing, therapy-resistant CRPS-I, at the University Medical Centre Groningen, The Netherlands, between May 2000 and September 2015 (n = 53) were invited to participate. Methods: Participants were interviewed in a semi-structured way regarding mobility, pain, recurrence of CRPS-I, quality of life, and prosthesis use. Those who reported recurrence of CRPS-I underwent physical examination. Results: A total of 47 patients (median age at time of amputation, 41.0 years; 40 women) participated. Longitudinal evaluation was possible in 17 participants. Thirty-seven participants (77%) reported an important improvement in mobility (95% confidence interval (95% CI) 63; 87%). An important reduction in pain was reported by 35 participants (73%; 95% CI 59; 83%). CRPS-I recurred in 4 of 47 participants (9%; 95% CI 3; 20%), once in the residual limb and 3 times in another limb. At the end of the study of the 35 participants fitted with a lower limb prosthesis, 24 were still using the prosthesis. Longitudinal evaluation showed no significant deteriorations. Conclusion: Amputation can be considered as a treatment for patients with long-standing, therapy-resistant CRPS-I. Amputation can increase mobility and reduce pain, thereby improving the quality of patients' lives. However, approximately one-quarter of participants reported deteriorations in intimacy and self-confidence after the amputation.